2022
DOI: 10.3389/fphar.2022.973768
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of Withania somnifera, AYUSH-64, and remdesivir on the activity of CYP-450 enzymes: Implications for possible herb−drug interactions in the management of COVID-19

Abstract: Ayurvedic medicines Withania somnifera Dunal (ashwagandha) and AYUSH-64 have been used for the prevention and management of COVID-19 in India. The present study explores the effect of Ashwagandha and AYUSH-64 on important human CYP enzymes (CYP3A4, CYP2C8, and CYP2D6) to assess their interaction with remdesivir, a drug used for COVID-19 management during the second wave. The study also implies possible herb−drug interactions as ashwagandha and AYUSH-64 are being used for managing various pathological condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…Withaferin A, which is another Withanolide derived from WS, has also been shown to possess anti-viral and immunomodulatory activity as per the in-silico studies ( 26 ). A detailed characterization of the active ingredients of WS along with other herbal extracts was reported recently by our group, in which the in-vitro anti-viral activity of WS extract components was shown for the first time ( 28 ). On the other hand, TC, another important herbal extract, has also been previously used and shown to have anti-viral potential through docking studies ( 25 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Withaferin A, which is another Withanolide derived from WS, has also been shown to possess anti-viral and immunomodulatory activity as per the in-silico studies ( 26 ). A detailed characterization of the active ingredients of WS along with other herbal extracts was reported recently by our group, in which the in-vitro anti-viral activity of WS extract components was shown for the first time ( 28 ). On the other hand, TC, another important herbal extract, has also been previously used and shown to have anti-viral potential through docking studies ( 25 ).…”
Section: Discussionmentioning
confidence: 92%
“…The filtrate obtained was assumed to be 100% aqueous extract which was further diluted in water to achieve a dosing concentration. The filtrate was further used for evaluating the composition and was previously published ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of information and scientific validation of activities reported for various plants parts of W. somnifera . Several activities including neuroprotection (Ahmad, Samuel, e al, 2016, Ahmad, Arya, et al, 2016), inflammatory (Chauhan et al, 2022), bone health (Khedgikar et al, 2013) anti‐cancer (Siddique et al, 2014; Sivasankarapillai et al, 2020; Yadav et al, 2022), antioxidant and, anti‐diabetic (Mikulska et al 2023) anti‐viral specially in Covid management (Kasarla et al, 2022) have been illustrated earlier wherein plant has shown promising effect (Fig. 1).…”
Section: Withania Somnifera: Therapeutically Potential Activitiesmentioning
confidence: 99%
“…Withania somnifera Dunal (ashwagandha) and AYUSH‐64 were explored due to their possible action on human Cytochrome P450 enzymes to examine their interaction with remdesivir. The study has shown probable herb–drug interactions from AYUSH‐64 in managing different pathological conditions (Kasarla et al, 2022). Similarly, the phytochemicals of plants were studied in silico through docking for their inhibitory activity against various targets, including angiotensin‐converting enzyme 2 (ACE‐2), the SARS‐CoV‐2 receptor, and so on (Singh et al, 2022).…”
Section: Withania Somnifera: Therapeutically Potential Activitiesmentioning
confidence: 99%